Enhancing telehealth services development in Pakistani healthcare sectors through examining various medical service quality characteristics - Saifullah; Ma, Zhiqiang; Li, Mingxing; Maqbool, Muhammad Qasim; Chen, Jing (Frontiers in Public Health, 2024)
The telehealth service increased attention both during and after the Covid-19 outbreak.Nevertheless, there is a dearth of research in developing countries, including Pakistan. Hence, the objective of this study was to examine telehealth service quality dimensions to promote the telehealth behavior intention and sustainable growth of telehealth in Pakistan.This study employed a cross-sectional descriptive design. Data were collected from doctors who were delivering telehealth services through a well-designed questionnaire. To examine the hypothesis of the study, we employed the Smart PLS structural equation modeling program, namely version 0.4.The study findings indicate that medical service quality, affordability, information quality, waiting time, and safety have a positive impact on the intention to engage in telehealth behavior. Furthermore, the adoption of telehealth behavior has a significant favorable effect on the actual utilization of telehealth services, which in turn has a highly good impact on sustainable development.The study determined that telehealth services effectively decrease the amount of time and money spent on travel, while still offering convenient access to healthcare. Furthermore, telehealth has the potential to revolutionize payment methods, infrastructure, and staffing in the healthcare industry. Implementing a wellstructured telehealth service model can yield beneficial results for a nation and its regulatory efforts in the modern age of technology.